Clinical presentation and transmission of postnatal cytomegalovirus infection in preterm infants - Lee, Jun Eon; Han, Yea Seul; Sung, Tae-Jung; Kim, Dong Hyun; Kwak, Byung Ok (Frontiers in Pediatrics, 2022)
Background: Preterm infants are at greater risk of developing postnatal cytomegalovirus (CMV) infection with serious symptoms. Breast milk is the main route of CMV transmission in populations with a high seroprevalence. Objectives: This study aimed to investigate the clinical presentation and transmission of postnatal CMV (pCMV) infection via breast milk in preterm infants under the specific setting of our NICU. Methods: The medical records of 147 preterm infants were reviewed retrospectively, and their clinical characteristics and outcomes were analyzed. Breast milk and infant urine samples were collected every two weeks until discharge, and the kinetics of CMV loads were evaluated using a polymerase chain reaction assay. Results: Seventeen infants (11.6%) were diagnosed with pCMV infection during the study period. In comparison between the pCMV and control groups, the mean birth weight was significantly lower in the pCMV group than in the control group (1084.1±404.8g vs. 1362.5±553.8g, p = 0.047). Four (23.5%) patients had leukocytopenia, six (35.3%) had neutropenia, three (17.6%) had thrombocytopenia, and two (11.8%) had hyperbilirubinemia in the pCMV group. Five patients were treated with antiviral agents, and their CMV load in the urine decreased after treatment. CMV loads peaked at 3–5 weeks in breast milk, whereas they peaked at 8–12 weeks of postnatal age in infants’ urine. A comparison between the median CMV load in breast milk from the pCMV and control groups revealed a significant difference (p = 0.043). Conclusion: Most preterm infants with pCMV infection present a favorable clinical course and outcomes. A high CMV viral load in breast milk is associated with transmission. Further studies are warranted to prevent transmission and severe pCMV infections in preterm infants.